Human resource skill adjustment in service sector: Predicting dynamic capability in post COVID-19 work environment - Nurul Mohammad Zayed; Friday Ogbu Edeh; Saad Darwish; K. M. Anwarul Islam; Halyna Kryshtal; Vitalii Nitsenko; Olena Stanislavyk (Journal of Risk and Financial Management, 2022)
The havoc caused by the COVID-19 pandemic on hospitality businesses across the world affected the human resource skills of the industry to the extent that managers and industry experts are still finding difficult how best to upgrade the skills of their workforce and enhance their capability to withstand future disruptions. It is based on this problem that this research investigated the effect of human resource skill adjustment on the dynamic capability of hospitality businesses in sub-Saharan Africa post the COVID-19 work environment. The study employed cross-sectional survey design with a total population of two hundred and twenty participants drawn from sixty hospitality businesses in the south-eastern part of Nigeria. Formulated research hypotheses were analysed with linear regression. The results of the research demonstrated that human resource skill adjustment predicted the dynamic capability of hospitality businesses. The study concludes that human resource skill adjustment measured with upskilling and reskilling methodologies predicted the dynamic capability. The implication of the finding is that managers and operators of hospitality businesses should implement human resource skill adjustment in all the functional areas of their management to enable each section or department to attain its goals equally, and enhance the dynamic capability of the industry.
Keywords: 650; COVID-19; dynamic capability; hospitality industry; human resource skill adjustment; post COVID-19